Edutainment as a Preventive Tool for Adolescent Risk Behavior: A Systematic Analysis of HIV/AIDS Education Strategies - Salsabilla, Nendy Putra; Sulistyowati, Muji; Oktaviana, Riska; Astuti, Aldiella Ayu Prasetya; Pambudi, Tesalonika Arina (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Adolescent engagement in risky sexual behaviors, such as early sexual initiation, presents a pressing global public health concern that impacts adolescents’ physical and mental health and may influence their prospects. These behaviors increase risks of HIV/AIDS, other sexually transmitted infections, and unintended pregnancies, which can limit opportunities and affect life trajectories. According to the World Health Organization (WHO), adolescents represent around 20% of the global population, with the majority living in developing nations where resources for education and prevention are often limited. Data from Indonesia’s National Population and Family Planning Board (BKKBN) highlights this challenge, with 60% of adolescents aged 16–17, 20% aged 14–15, and 20% aged 19–20 reporting sexual activity. Objectives: This systematic review investigates the effectiveness of edutainment—a strategy combining education with entertainment—in reducing risky sexual behaviors among adolescents by preventing HIV/AIDS and promoting informed decision-making. Methods: Literature from 2014–2024 was gathered using Proquest, Google Scholar, PubMed, Elsevier, and Web of Science, with keywords including "edutainment," "prevention of casual sex," "adolescent sex education," and "sex education programs. Results: Findings indicate that edutainment approaches—utilizing interactive play and educational activities—effectively enhance adolescent and parental awareness of the risks associated with free sex and strengthen adolescent skills in self-protection and resisting inappropriate advances. Conclusion: The edutainment-based intervention model is a promising strategy for preventing risky sexual behaviors among adolescents, promoting health-conscious decision-making, and fostering protective skills.